Quarternization of 3-azido-1-propyne oligomers obtained by copper(I)-catalyzed azide–alkyne cycloaddition polymerization - Nakano, Shun; Hashidzume, Akihito; Sato, Takahiro (Beilstein Journal of Organic Chemistry, 2015)
3-Azido-1-propyne oligomer (oligoAP) samples, prepared by copper(I)-catalyzed azide–alkyne cycloaddition (CuAAC) polymerization, were quarternized quantitatively with methyl iodide in sulfolane at 60 °C to obtain soluble oligomers. The conformation of the quarternized oligoAP in dilute DMSO-d6 solution was examined by pulse-field-gradient spin-echo NMR based on the touched bead model.
Keywords: 3-azido-1-propyne oligomer; CuAAC polymerization; hydrodynamic radius; methyl iodide; pulse-field-gradient spin-echo NMR; quarternization